Perinatal and maternal outcome in meconium stained amnioticfluid (thin and thick) at dhiraj general hospital, a rural tertiary health centre - Shukla, Jitendra V.; Patel, Arpana D.; Chandrayan, Piyush (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: To determine the perinatal outcome of with Meconium-stained amniotic fluid (MSAF) compared with clear amniotic fluid at Dhiraj Hospital. Methods: A prospective observational study was carried out in obstetrics and gynaecology department of Dhiraj Hospital, Sumandeep Vidyapeeth from March 2021 to August 2021. All patients fulfilling inclusion and exclusion criteria as mentioned above were taken for the study. All the categorial variables were analysed independently with the help of chi square test and fisher’s exact test and all the continuous variables were analysed with independent ‘t test’. Results: Out of 500 patients selected for the present study which had inclusion criteria, 13.6% were meconium stained out of which 50 (73.5%) cases had thin meconium and 18 (26.4%) cases had thick meconium. Fetal CTG abnormalities were more common in MSAF group and were noted in 38.2% of cases which is significantly increased compared to control group with CTG abnormalities in 8.3%. The difference was significant with p value of <0.001. 32(47.0%) patients with meconium-stained amniotic fluid had normal vaginal delivery, while in control group out of 432, 360 (83.3%) delivered normally. Incidence of LSCS and assisted vaginal delivery was more in meconium-stained amniotic fluid. Conclusions: Meconium-stained amniotic fluid is associated with more frequency of operative delivery, birth asphyxia, neonatal sepsis, and neonatal intensive care unit admissions compared to clear amniotic fluid. Better perinatal outcome in clear amniotic fluid compared to meconium stained liquor.